Control of charge dynamics by blending ZnO nanoparticles with poly(3-hexylthiophene) for efficient hybrid ZnO nanorods/polymer solar cells - Pipat Ruankham (2018)
© 2015, Springer-Verlag Berlin Heidelberg. Photovoltaic performances of hybrid ZnO nanorods/polymer solar cells have been improved by controlling their charge dynamics through addition of ZnO nanoparticles into poly(3-hexylthiophene) (P3HT) photoactive layer. The inter-rod space of ZnO nanorod substrates is completely filled with the solution-processed ZnO nanoparticles/P3HT blends, forming homogeneous junction among the components. The optimum PCE of 1.020 % has been achieved from the device with 13 vol % ZnO nanoparticles loaded. The enhancement in external quantum efficiency has been also observed, indicating the improved excitons separation at the ZnO/P3HT interface. The information on charge dynamics in the system has been investigated by electrochemical impedance spectroscopy. It has been found that the additional space-charge layer formed at the ZnO nanoparticles–contact electrode interface is a reason behind the improvement of open-circuit voltage. Moreover, the formation of ZnO nanoparticles domain extending across the active layer and the percolation path for charge carriers promotes charge transport by reducing transit time of the carriers, extending charge carrier lifetime and enhancing the charge transfer at the ZnO/P3HT interface. Interestingly, it has been found that charge transport in the devices does not limit the device performances, even for the 400-nm-thick active layer.